Circles within a Circle: The Condition for the Possibility of Ethical Business Institutions Within a Market System - Allinson, Robert Elliott (Journal of business ethics, 2004)
How can a business institution function as an ethical institution within a wider system if the context of the wider system is inherently unethical? If the primary goal of an institution, no matter how ethical it sets out to be, is to function successfully within a market system, how can it reconcile making a profit and keeping its ethical goals intact? While it has been argued that some ethical businesses do exist, e.g., Johnson and Johnson, the argument I would like to put forth is that no matter how ethical a business institution is, or how ethical its goals are, its capacity to act in an ethical manner is restricted by the wider system in which it must operate, the market system. Unless there is a fundamental change in the notion of the market system itself, the capacity for individual businesses to act in an ethical manner will always be restricted. My argument is divided into two parts. The first part is to show the inherent bias towards unethical outcomes that is inherent in the market system. The second part is to suggest how to reorient the general economic framework in order to make ethical institutions more possible. The question then becomes, how to define economic behavior in terms other than competition for profit.